Oral ATP treatment in alternating hemiplegia of childhood: a case report and review - Marco Carrozzi; Maria Elisa Morelli; Mario Cirino; Alessandra Maestro; Gilda Paternuosto; Giulia Benericetti; Giada Bennati; Maura Bin; Anna Flamigni; Federico Pigato; Natalia Maximova; Egidio Barbi; et al. (Frontiers in Medicine)
Alternating hemiplegia of childhood (AHC) is a rare neurological disorder that usually manifests before 18 months of age and is characterized by recurrent, alternating episodes of hemiparesis with variable frequency and can last from a few minutes to several days. We present a case of AHC in a little girl carrying a sporadic mutation in the ATP1A3 gene (p.Glu815Lys) refractory to flunarizine and non-compliant to topiramate due to adverse effects treated with oral compound of adenosine-5′-triphosphate (ATP) capsules. Outcome was evaluated through the follow-up and side effects and safety were monitored regularly. Compounded drug showed effectiveness and safety. Indeed, during the four-year follow-up, with the dose of adenosine-5′-triphosphate gradually increasing up to 21 mg/kg, the patient showed a substantial benefit in controlling the frequency and duration of hemiplegic episodes and an improvement in neurological deterioration.